(untitled) (BIBECHANA, 2024)
Crusher run dust is a waste product produced in significant quantities during the removal and processing of rocks at crusher plants. This experiment examines how high-performance concrete characteristics are affected when sand is partially replaced with crusher-run dust in various ratios. The replacement of fine aggregate with crusher run dust has been considered for M50 grade design mix concrete with 0%, 15%, 30%, 45%, and 60%, and the change in characteristics has been considered. To keep the workability between 76mm and 85mm, a superplasticizer was utilized. In this experimental investigation, the mechanical properties of concrete such as compressive strength, flexural strength, split tensile strength, and porosity have been examined. Concrete’s characteristics showed improvement. Crusher-run dust with a 30% concentration in concrete has produced the best results.